Integrative transcriptome and phenome analysis reveal unique regulatory cascades controlling the intraerythrocytic asexual and sexual development of human malaria parasites - Birkholtz, Lyn-Marie (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2018.